1832. Concordance in End-of-Life Antimicrobial Prescribing Practices among Medicine Subspecialists. (26th November 2018) - Datta, Rupak; McManus, Dayna; Topal, Jeffrey; Sanft, Tara; Quagliarello, Vincent; Dembry, Louise Marie; Morrison, Laura; Juthani-Mehta, Manisha
Abstract: Background: Evaluating end-of-life (EOL) antimicrobial prescribing practices may guide stewardship efforts. Methods: We conducted a 27-item survey of attending physicians, physician assistants, and nurse practitioners at Yale New Haven Hospital from January 2018 to February 2018 using REDCap. Results: Of 275 providers surveyed, 109 (40%) responded. Regardless of specialty, most consider withholding antimicrobials at EOL ( n = 73/109, 67%), view IV antimicrobials as escalation of care ( n = 66/109, 61%), believe decision-making should involve patients and providers ( n = 101/109, 93%), and recognize diarrhea as an adverse effect ( n = 97/109, 89%; Table 1). However, among the subset who conduct advance care planning ( N = 82), only 49% ( N = 40/82) discuss antimicrobials. Conclusion: Despite agreement in EOL prescribing practices across specialties, antimicrobials are not routinely addressed during advance care planning. These data support the integration of antimicrobial use into advance care plans linked to stewardship programs. Disclosures: M. Juthani-Mehta, Iterum Therapeutics: Scientific Advisor, Consulting fee.